2013
DOI: 10.1186/1743-422x-10-132
|View full text |Cite
|
Sign up to set email alerts
|

A mobile genetic element with unknown function found in distantly related viruses

Abstract: BackgroundThe genetic element s2m seems to represent one of very few examples of mobile genetic elements in viruses. The function remains obscure and a scattered taxonomical distribution has been reported by numerous groups.MethodsWe have searched GenBank in order to identify all viral accessions that have s2m(−like) sequence motifs. Rigorous phylogenetic analyses and constrained tree topology testing were also performed in order to investigate the apparently mobile nature of s2m.ResultsThe stem-loop s2m struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 22 publications
(28 reference statements)
1
92
1
1
Order By: Relevance
“…The RNA family analysis by Rfam suggested presence of two motifs matching to corona virus stem loop II (s2m) motif in the 3′-UTR as reported for other astroviruses (Jonassen et al 1998;. Although, exact function is still not uncovered, the presence of these "s2m" motifs is believed to influence gene expression through RNA-interference mechanism (Tengs et al 2013) Based on the nucleotide similarity, the virus was found to be closest to the chicken astrovirus isolate GA2011 (Kang et al 2012) followed by CAstV/4175 (direct submission) Fig. 2 Phylogenetic relatedness of chicken astrovirus isolate CAstV/India/Anand/2016 based on whole genome sequence using neighbour joining method with 1000 bootstraps suggested that this limited identity of capsid protein of the CAstV/Poland/G059/2014 isolate with other chicken astrovirus capsid protein but higher identity with the duck astroviruses may be due a recombination event and shared ancestors with the duck astroviruses.…”
Section: Discussionmentioning
confidence: 85%
“…The RNA family analysis by Rfam suggested presence of two motifs matching to corona virus stem loop II (s2m) motif in the 3′-UTR as reported for other astroviruses (Jonassen et al 1998;. Although, exact function is still not uncovered, the presence of these "s2m" motifs is believed to influence gene expression through RNA-interference mechanism (Tengs et al 2013) Based on the nucleotide similarity, the virus was found to be closest to the chicken astrovirus isolate GA2011 (Kang et al 2012) followed by CAstV/4175 (direct submission) Fig. 2 Phylogenetic relatedness of chicken astrovirus isolate CAstV/India/Anand/2016 based on whole genome sequence using neighbour joining method with 1000 bootstraps suggested that this limited identity of capsid protein of the CAstV/Poland/G059/2014 isolate with other chicken astrovirus capsid protein but higher identity with the duck astroviruses may be due a recombination event and shared ancestors with the duck astroviruses.…”
Section: Discussionmentioning
confidence: 85%
“…An event of this type has recently been described in which a 55nt-long translation enhancer element was acquired by Melon necrotic spot virus (family Tombusviridae ) from Cucurbit aphid-borne yellow virus (family Luteoviridae ) (Miras et al, 2014). A similar process likely accounts for the presence of the 43nt-long stem-loop-2-like motif (s2m) in the 3’-UTRs of members of Astroviridae, Caliciviridae, Coronaviridae and Picornaviridae (Tengs et al, 2013). The HCV IRES retains its activity despite substitution of domain II by analogous elements from other Type IV IRESs (Reusken et al, 2003; Boerneke et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in line with previous observations (Brian and Baric, 2005;Masters, 2007;Sola et al, 2011b), the study confirms a significant degree of variation in the 3 -terminal region of the 3 UTR, with the conserved octanucleotide sequence being consistently located in a single-stranded region of a stem-loop structure. Interestingly, specific lineages of beta-, gamma-and deltacoronaviruses (as well as other plus-strand RNA viruses) may contain another structural element, called s2m, in the 3 UTR, thus further adding to the variability of this genome region in coronaviruses (Jonassen et al, 1998;Robertson et al, 2005;Tengs et al, 2013). The conservation pattern of the various lineage-specific structural elements argues against a conserved function in viral RNA synthesis but rather suggests that the 3 UTR may contain elements that are involved in specific virushost interactions and/or pathogenesis as has been shown for the MHV HVR (Goebel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%